Measuring the impact of international tools in local governance: The new urban diplomacy - Tamara Espiñeira-Guirao (Rozwój Regionalny i Polityka Regionalna)
Which is the added-value of the international action of cities? Is this action legitimate? Our analysis proposes to invert the famous slogan and get local authorities to think local and act global. This reversed framework, that we may call “new urban diplomacy” focuses on governance and more specifically in the urban project, understood as the policy agenda of the city council. Based on active subsidiarity, local development moves through new urban diplomacy to a foreground where European policies are a tactical choice among other planning tools. Thus, in order to explore how this framework works, our analysis will examine three categories of instruments: programming, communication and representation, notwithstanding with the role of city networks. Our proposal to structure this new urban diplomacy is the result of a process of participatory observation (almost 15 years) supported by grounded theory. Three main approaches of the international role of cities rooted our analysis: economic (global cities, city branding), political (governance, international relations) and geographical (territorial development, urban planning). So as to define the contours of new urban diplomacy as a lever for the urban project, this proposal presents three main indicators (capacity, intensity and coordination) and three possible scenarios (the bywatcher, the silent silo and the strategist). Our results highlight two key factors: one external (the europeanisation processes of local authorities) and another internal (talent, perceived both as the implication of the municipality and the creation of a local think tank, that we called Noodle). Our final goal is to offer a guide for analysis and further research. This guide should also serve cities in search of additional tools for their urban project.